Diversity, Ecology, Biogeography, and Evolution of the Prevalent Brown Algal Genus Lobophora in the Greater Caribbean Sea, Including the Description of Five New Species1. Issue 3 (4th May 2020) - Vieira, Christophe; Morrow, Kathleen; D'Hondt, Sofie; Camacho, Olga; Engelen, Aschwin H.; Payri, Claude E.; De Clerck, Olivier
Abstract : Distributed in tropical and warm‐temperate waters worldwide, Lobophora species are found across the Greater Caribbean (i.e., Caribbean sensu stricto, Gulf of Mexico, Florida, the Bahamas, and Bermuda). We presently discuss the diversity, ecology, biogeography, and evolution of the Greater Caribbean Lobophora species based on previous studies and an extensive number of samples collected across the eastern, southern, and to a lesser extent western Caribbean. A total of 18 Lobophora species are now documented from the Greater Caribbean, of which five are newly described ( L. agardhii sp. nov., L . dickiei sp. nov., L. lamourouxii sp. nov., L . richardii sp. nov., and L. setchellii sp. nov.). Within the Greater Caribbean, the eastern Caribbean and the Central Province are the most diverse ecoregion and province (16 spp.), respectively. Observed distribution patterns indicate that Lobophora species from the Greater Caribbean have climate affinities (i.e., warm‐temperate vs. tropical affinities). In total, 11 Lobophora species exclusively occur in the Greater Caribbean; six are present in the western Atlantic; two in the Indo‐Pacific; and one in the eastern Pacific. Biogeographic analyses support that no speciation occurred across the Isthmus of Panama, and that the Greater Caribbean acted as a recipient region for species from the Indo‐Pacific and as a region of diversification as well as a donor region to the North‐eastern Atlantic. The Greater Caribbean is not an evolutionary dead end for Lobophora, but instead generates and exports diversity. Present results illustrate how sampling based on DNA identification is reshaping biogeographic patterns, as we know them.